Twinning with zero twinning shear. (December 2016) - Li, B.; Zhang, X.Y.
Abstract: It is generally believed that the 10 1 − 2 10 1 − 1 − twinning shear in magnesium equals 0.129 and twin growth is mediated by twinning dislocations. Starting from these notions, we analyze, in great detail, the lattice transformation from parent to twin, and prove that the twinning shear cannot be any finite value but zero. Thus, no twinning dislocations should be involved in this twinning mode and the lattice transformation is solely accomplished by atomic shuffling. Atomistic simulations and high resolution transmission electron microscopy observations unambiguously confirm our conclusion. Graphical abstract: